Analisis Model Mental Siswa pada Materi Larutan Elektrolit dan Nonelektrolit: Studi Kasus di Pandeglang - Dinda Novia; Achmad; Yuli, (Jurnal Riset Pendidikan Kimia (JRPK), 2018)
This research aimed to analyse the students’ mental models of one of schools in Pandeglang in electrolyte and non-electrolyte solutions learning. The participants were year X students in science program. The method employed case study on understanding the participants’ background. The data collection techniques of observation, interview, reflective journal free words association, and free drawing techniques. The research results showed that the students constructed mental based on their understanding and experiences, assisted with the analogies that they constructed which is influenced by their characteristics and environment. The examples were the students analogized ion that freely moves in electrolyte and non-electrolyte solutions with fish, bees and goats, while ionic bond was analogized with sadaqah, zakat, and waqf. The students’ mental models on the learning material of electrolyte and non-electrolyte solutions were divided into mental model that was consistent with the concept and the mental model that deviated from the concept. The discrepancy of the student’s mental models was influenced by their understanding and experiences. Keywords: mental model, case study, electrolyte and non-electrolyte solutions